Self-Efficacy as Mediator: The Impact of Entrepreneur Education on Entrepreneur Intention - Rr Fosa Sarassina (Politeknik Negeri Batam, 2020)
The literature review shows inconsistent results of the relationship between entrepreneurial education withentrepreneurial intention and recommends the investigation of the role of self-efficacy as a mediator between the two constructs. This study aims to meet that purpose. From the response of 241 students in Jogjakarta, which was analyzed using structural equation modeling (SEM), it is concluded that self-efficacy mediates the relationship. This finding signifies the role of entrepreneurship education as it builds self-efficacy to become an entrepreneur, which in turn increases the intention to become one.